LITERATURE REVIEW WET CUPPING TECHNIQUE ON URIC ACID LEVELS IN PATIENTS WITH HYPERURICEMIA - Firdaus, Firdaus; Hasina, Hasina; Hilmi, Arif (International Journal of Islamic and Complementary Medicine, 2023)
Uric acid is an acid that is formed as a result of purine metabolism in the body. Higher levels of uric acid in the blood will cause an inflammatory reaction or inflammation that causes swelling, redness, and pain. The prevalence of suffering from uric acid (gout) in Dharmas Raya is 754 elderly Indonesians. The purpose of the literature review is to review the effect of cupping on gout. The literature review is carried out based on issues. In the literature review, this journal uses an average of 5 research journals using pre-experimental with pre-test - post-test design. The literature review strategy according to the PICO and the journals used for the literature review was obtained through data from national and international journal providers through Google Scientist.: Based on 5 studies it was found that one of the results was obtained. The statistical analysis used in this study is statistical analysis. paired t-test. Uric acid levels before and after cupping therapy were 4.91 and 4.33, respectively. Based on the t-test of differences in blood uric acid levels before and after cupping therapy, the value of t = 2.46 (p = 0.02) p-value is smaller than (a = 0.05) this indicates that there is a difference in blood acid levels before and after cupping therapy significantly. From these 5 journal studies, it can be said that wet cupping therapy can reduce uric acid levels.